Familial Hemiplegic Migraine with Severe Attacks: A New Report with ATP1A2 Mutation. (13th October 2016) - Martínez, E.; Moreno, R.; López-Mesonero, L.; Vidriales, I.; Ruiz, M.; Guerrero, A. L.; Tellería, J. J.
Abstract : Introduction . Familial hemiplegic migraine (FHM) is a rare disorder characterized by migraine attacks with motor weakness during the aura phase. Mutations in CACNA1A, ATP1A2, SCN1A, and PRRT2 genes have been described. Methods . To describe a mutation in ATP1A2 gene in a FHM case with especially severe and prolonged symptomatology. Results . 22-year-old woman was admitted due to migraine-type headache and sudden onset of right-sided weakness and aphasia; she had similar episodes in her childhood. Her mother was diagnosed with hemiplegic migraine without genetic confirmation. She presented with fever, decreased consciousness, left gaze preference, mixed aphasia, right facial palsy, right hemiplegia, and left crural paresis. Computed tomography (CT) showed no lesion and CT perfusion study evidenced oligohemia in left hemisphere. A normal brain magnetic resonance (MR) was obtained. Impaired consciousness and dysphasia began to improve three days after admission and mild dysphasia and right hemiparesis lasted for 10 days. No recurrences were reported during a follow-up of two years. We identified a variant in heterozygous state in ATP1A2 gene (p.Thr364Met), pathogenic according to different prediction algorithms (SIFT, PolyPhen2, MutationTaster, and Condel). Conclusion . Prolonged and severe attacks with diffuse hypoperfusion in a FHM seemed to be specially related to ATP1A2 mutations, and p.T364M should be considered.